Mascot Design of Zara and Vano as a Marketing Strategy for Zabava Labs - Shafa, Qinan Nazratulya; Hasbullah; Sumadewa, I Nyoman Yoga (MultiTech Publisher, 2024)
The development of online games is in line with advances in computer and network technology, including Web3 which includes the use of Blockchain, smart contracts and decentralization. One company operating in this field is Zabava Labs, located in Singapore, with their flagship product, Sentinel Haven. Although Zabava Labs is active on social media, especially Instagram, the visual image of their feed does not represent the company effectively, which results in low audience engagement and interest. This research aims to design a character mascot that is attractive to young gamers in Indonesia to improve the image and interaction of Zabava Labs on social media. The designed mascot is expected to be able to build the company brand by providing a lasting impression, facilitating effective communication with the audience, and increasing brand recognition in the market. Through a creative and innovative design approach, this mascot will become a visual element that is not only attractive, but also reflects a strong and memorable brand.